Tafsir Al-Qur’an tentang Artificial intelligence (AI) dan Etika dalam Berteknologi - Jefri Arian Syahputra; Ali Akbar (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The advancement of Artificial Intelligence (AI) has profoundly influenced multiple aspects of human life. This article explores AI applications across key sectors, including automotive, military, education, healthcare, food industry, and transportation. In the automotive field, AI enhances vehicle maintenance and fault diagnosis efficiency. Within the military, AI contributes to the development of autonomous defense systems such as combat robots and drones. In education, it supports adaptive learning and intelligent teaching robots. In both the food and healthcare industries, AI accelerates analytical processes, ensures quality control, and enables more accurate medical diagnoses. Furthermore, AI plays a crucial role in transportation by advancing autonomous vehicles and environmentally friendly mobility systems. The article concludes that AI has brought significant benefits and innovations to human civilization. However, ethical oversight remains essential to ensure that AI development aligns with human values and contributes positively to a sustainable and intelligent future.